Simulation of water and chemical transport of chloride from the forest ecosystem to the stream. (April 2021) - Zanchi, Giuliana; Yu, Lin; Akselsson, Cecilia; Bishop, Kevin; Köhler, Stephan; Olofsson, Jörgen; Belyazid, Salim
Abstract: The study evaluates the biogeochemical model ForSAFE-2D, designed to simulate water and chemical transport from the forest to the stream, by simulating the hydrology and the transport of the chemical tracer chloride (Cl − ) along a forest hillslope in Northern Sweden. The simulated Cl − exports were in balance with the simulated inputs but measurements suggested a net release of Cl − from the catchment. Underestimated deposition inputs (deposition peaks and possibly dry deposition) were probably and partially responsible for this mismatch. However, we could not exclude that other soil biogeochemical processes omitted in ForSAFE-2D could also contribute to Cl − exports from the catchment. The study showed that ForSAFE-2D is a promising tool to better understand the factors that regulate the chemical export from the forest to the stream. The results also confirmed that there are limitations in using Cl − as a tracer in forest ecosystems. Highlights: ForSAFE-2D simulates lateral water and water chemistry flows on a forest hillslope. It did not simulate a net catchment release of Cl − as indicated by measurements. The net release might be a consequence of unaccounted deposition inputs. Soil processes not included in the model could partially contribute to Cl − exports.